A 5‐color flow cytometric method for extended 8‐part leukocyte differential. Issue 6 (5th April 2017) - Guy, Julien; Wagner‐Ballon, Orianne; Pages, Olivier; Bailly, François; Borgeot, Jessica; Béné, Marie‐C; Maynadié, Marc
Abstract : Objectives: Microscopic leukocyte differentials display many drawbacks. Several single 5 to 8‐color tubes using multiparameter flow cytometry (MFC) are able to provide extended differentials with sequential gating‐based analysis strategies. We investigated a new 5‐color MFC method to perform an extended 8‐part differential with a simplified gating strategy. Methods: Whole blood was stained with a combination of antibodies including HLA‐DR‐FITC/CD19‐PE/CD45‐ECD/CD16‐PC5 + CD71‐PC5/CD5‐PC7. Results: An original approach was developed to exclude debris and straightforwardly gate the cells to identify sixteen populations. Strong correlations were obtained with the analyzer for neutrophils, lymphocytes, monocytes, and eosinophils ( R 2 >0.9). Abnormal cells, such as immature granulocytes and blast cells were identified with a good sensitivity and excellent correlation against cytomorphologic review ( R 2 =0.66 and 0.99, respectively). The choice of HLA‐DR and CD5 improved specificity for the identification of activated T‐lymphocytes and some lymphoid neoplastic cells, respectively. Conclusions: Here a new cytometric differential is proposed with a robust gating strategy which may be used even by unskilled cytometrists and can be easily automated. © 2017 International Clinical Cytometry Society